Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1128/aem.01069-08
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Nanoscale Elemental Silver Particles via Enzymatic Reduction by Geobacter sulfurreducens

Abstract: Geobacter sulfurreducens reduced Ag(I) (as insoluble AgCl or Ag؉ ions), via a mechanism involving c-type cytochromes, precipitating extracellular nanoscale Ag(0). These results extend the range of metals known to be reduced by Geobacter species and offer a method for recovering silver from contaminated water as potentially useful silver nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 19 publications
(20 reference statements)
2
70
1
3
Order By: Relevance
“…Silver is an element that has been used widely in industrial processes as diverse as photographic processing, catalysis, mirror production, electroplating, alkaline battery production, and jewelry making (18). It has been known for some time that silver ions and silver-based compounds can be highly toxic to microorganisms, and with increasing concern about pathogenic "superbugs" with high resistance to conventional antibiotics, silver is attracting much interest as a potential biocide (11,18,36,42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Silver is an element that has been used widely in industrial processes as diverse as photographic processing, catalysis, mirror production, electroplating, alkaline battery production, and jewelry making (18). It has been known for some time that silver ions and silver-based compounds can be highly toxic to microorganisms, and with increasing concern about pathogenic "superbugs" with high resistance to conventional antibiotics, silver is attracting much interest as a potential biocide (11,18,36,42).…”
mentioning
confidence: 99%
“…It has been known for some time that silver ions and silver-based compounds can be highly toxic to microorganisms, and with increasing concern about pathogenic "superbugs" with high resistance to conventional antibiotics, silver is attracting much interest as a potential biocide (11,18,36,42). Silver has no known physiological functions and can exist in several oxidation states, although it is most commonly encountered in its elemental [Ag(0)] and monovalent [Ag(I)] forms.…”
mentioning
confidence: 99%
“…The detected size of AgNPs synthesized by S. chartarum may agree or differ with previous scientific papers, this may be due to the species type, incubation period or environmental conditions of microbial growth. Size of AgNPs was 5-25, 10-100, 5-40, 200 and 500 nm produced by Aspergillus fumigates (Bhainsa and D'Souza, 2006), Cladosporium cladosporioides (Balaji et al, 2009), Trichoderma viride (Fayaz et al, 2010), Geobacter sulfurreducens (Law et al, 2008) and Lactobacillus Strains (Nair and Pradeep, 2002) respectively. Also, from the extracellular secretion of Schizophyllum commune, Lentinus sajar-caju and Pycnoporus sanguineus, it is observed that nanoparticles size was 42.12, 89.76 and 120.6 nm respectively (Yen San and Mashitah, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The Chemical-free disinfection is considered to be an attractive alternative and it is usually associated with silver metal. While silver has been known to be a bactericide element for at least 1200 years, colloidal silver or silver MNPs have recently been recognized and tested in various applications as excellent antimicrobial agents because of their high biocide activity (Kong & Jang, 2008;Law, 2008;Pal et al, 2007). The antibacterial action of silver MNPs is still under debate but it has been reported to be similar to that of silver ions, which bind to DNA, block transcription, and therefore interrupt the bacterial respiration and the adenosine triphosphate synthesis.…”
Section: Biocide and Antibiofouling Applicationsmentioning
confidence: 99%